Strong coupling and vortexes assisted slow light in plasmonic chain-SOI waveguide systems - Giovanni Magno (Nature Portfolio, 2017)
Abstract A strong coupling regime is demonstrated at near infrared between metallic nanoparticle chains (MNP), supporting localized surface plasmons (LSP), and dielectric waveguides (DWGs) having different core materials. MNP chains are deposited on the top of these waveguides in such a way that the two guiding structures are in direct contact with each other. The strong coupling regime implies (i) a strong interpenetration of the bare modes forming two distinct supermodes and (ii) a large power overlap up to the impossibility to distinguish the power quota inside each bare structure. Additionally, since the system involves LSPs, (i) such a strong coupling occurs on a broad band and (ii) the peculiar vortex-like propagation mechanism of the optical power, supported by the MNP chain, leads to a regime where the light is slowed down over a wide wavelength range. Finally, the strong coupling allows the formation of guided supermodes in regions where the bare modes cannot be both guided at the same time. In other words, very high k modes can then be propagated in a dielectric photonic circuit thanks to hybridisation, leading to extremely concentrated propagating wave. Experimental work gives indirect proof of strong coupling regime whatever the waveguide core indexes.